A hybrid numerical technique for solving fractional Riccati equations (International Journal of Food and Nutritional Sciences, 2023)
In this article, we extends the application of hybrid numerical technique known as ‘Laplace adomian decomposition mehtod’ to the fractional Riccati equations. The hybrid numerical technique is the combination of Laplace transform and Adomian decomposition method. It increase the performance of the numerical technique and reduces the computing time. Finally, the efficiency of the proposed technique is shown by solving two examples and comparing the results with existing methods.